Sovereign Debt: Is to Forgive to Forget? - Bulow, Jeremy; Rogoff, Kenneth (American Economic Review, 1989)
We show that, under fairly general conditions, lending to small countries must be supported by the direct sanctions available to creditors, and cannot be supported by a country's "reputation for repayment." This distinction is critically important for understanding the true underlying structure of sovereign lending contracts, and comparing policy alternatives for dealing with the developing country debt problem.